AGRICOH, a newly formed consortium of agricultural cohorts. (19th October 2011) - Leon, ME; Freeman, Laura Beane; Douwes, Jeroen; Hoppin, Jane; Kromhout, Hans; Lebailly, Pierre; Nordby, KC; Schenker, Marc; Schüz, Joachim; Waring, SC; Alavanja, Michael; Annesi-Maesano, Isabelle; et al.
Abstract : Objectives: We recently formed AGRICOH, a consortium of agricultural cohort studies, offering the opportunity to investigate potential health effects of a wide range of occupational and environmental exposures coexisting in agriculture. Methods and results: AGRICOH is a consortium of 22 agricultural cohort studies initiated by US National Cancer Institute (NCI) and coordinated by International Agency for Research on Cancer (IARC) since October 2010. The consortium includes cohorts from 9 countries in 5 continents: South Africa (1), Canada (3), Costa Rica (2), USA (6), Korea (1), New Zealand (2), Denmark (1), France (3) and Norway (3). AGRICOH aspires to promote and sustain collaboration and pooling of data to investigate associations between a wide range of agricultural exposures (eg, pesticides, diesel exhausts, organic dust, inorganic dust, mycotoxins, endotoxins, viruses) and a wide range of health outcomes (eg, cancer, respiratory, neurologic, auto-immune diseases, as well as reproductive and allergic disorders and injuries), with a particular focus on associations that cannot easily be addressed in individual studies because of rare exposures (eg, use of infrequently applied pesticides) or relatively rare outcomes (eg, certain types of cancer, neurologic and auto-immune diseases). To facilitate future projects need for data harmonisation is required and underway. Characteristics of cohorts integrating AGRICOH, the wide range of exposures data available, data harmonisation challenges and research concepts will be illustrated. Conclusions: AGRICOH represents a great resource for conducting validation of exposure assessment and etiologic studies in association with a wide array of exposures unique to, or showing the highest likelihood of exposure, in the agricultural setting.